La lectura del posestructuralismo en Manfred Frank. El debate franco-alemán - Garnica, Naím (2019)
“The Reading of Post-structuralism in Manfred Frank. The German–French Debate”. The essay aims to reconstruct the reading of French thought by focusing on the lessons developed by Manfred Frank in his text What is Neo-structuralism? These lessons were key to the German reception of the French thought that emerged in the 60s. Frank’s lessons seem to offer some productive ways to think about the German reception of post-structuralism without falling into the rejection that led to the work of Jürgen Habermas in The Philosophical Discourse of Modernity. Our analysis focuses on the problem of subjectivity, which involves both the challenges that Frank proposes and the points that could be evidenced by poststructuralism. Finally, through the path marked by the lessons of Frank, the work suggests the possibility of a less problematic reception in the plane of German aesthetics.